Diving Tour Package Design With Business Model Canvas Approach At Nukila Dive Center Ternate, North Maluku - Moehamad Alfari Ramadhan; Asep Agus Handaka Suryana; Donny Juliandri Prihadi; Fanny Kristiandhi; Wahyuniar Pamungkas (Politeknik Pariwisata Makassar, 2024)
The development of marine tourism in Ternate has shown significant growth in recent years. The island offers marine ecotourism in the form of stunning underwater beauty, with beautiful coral reefs and rich marine biodiversity. Nukila Dive Center has an important role in the sustainability of tourism to support the tourism industry in Ternate. The business model approach is one of the important factors for the success of a company. The purpose of this study is to identify the Nukila Dive Center business model and identify the steps to create a conservation-based diving tour package. The business modeling method and the design of a conservation-based diving tour package are analyzed with nine elements of the business model canvas. Increasing value propositions, customer segments, and customer relationships will affect a company's income. Based on the results of the study, the elements of the business model at Nukila Dive Center were identified, namely the existing customer segments, namely domestic and foreign tourists. The value proposition offered is in the form of attractive underwater nature tourism. The current customer relationship is a direct relationship not only individually, but also with groups/diving communities and sea transportation associations. Revenue Streams received from diving trips, certification and equipment rental. Key resources in trip diving are the underwater beauty in the form of coral reefs and their ecosystems, as well as human resources. The existing key activities are trip diving and certification, Key partnerships currently carried out are travel agents, diving equipment providers, government agencies, diving communities. Cost Structures include ship fuel, equipment and facility maintenance, staff salaries. The prototype design that was made aims to be able to add value proposition to help add value at Nukila Dive Center to add new customer segments with the output of conservation-based diving tour packages in the form of e-flyers